INOVASI PENGGUNAAN JENIS LIPSTIK TERHADAP HASIL RIASAN LOOK BROWN UNTUK MACAM MACAM BENTUK BIBIR PADA TATA RIAS PENGANTIN MODERN - Anik Pujiati; Ifa Nurhayati; Florencia Angelina Bivan; Dinda Putri Nur Ngaeni4; Sakti Putri Prasetya; Maulida Firda Ayuningsih (Jurnal Genta Mulia, 2025)
Lipstick is an important element in bridal makeup as it enhances the character of the face through the color, texture, and shape of the lips. In the brown make-up look trend, brown lipstick is a popular choice because of the natural, warm, and elegant impression it gives. This research uses a descriptive qualitative method with data collection techniques through literature study, observation, interviews, and documentation. The results showed that lipstick types such as matte, gloss, tint, and cream provide different aesthetic effects on each lip shape, such as thin, thick, small, or asymmetrical lips, so their use needs to be adjusted to create a harmonious look. In conclusion, the choice of lipstick type and color in look brown bridal makeup not only strengthens the visual appeal but also reflects the personalization and confidence of the bride, so it is important for the makeup artist to consider the lip shape, client preference, and composition of the lipstick used.